Germination et croissance initiale de Neocarya macrophylla (Sabine) Prance, une espèce oléagineuse du Niger - Dan Guimbo, I.; Ambouta, KJM.; Mahamane, A.; Larwanou, M. (Tropicultura, 2011)
Germination and Initial Growth of Neocarya macrophylla (Sabine) Prance, a oleaginous Species of Niger. The study conducted in parallel in the real environment, nursery and laboratory to better understand the characteristics of germination and seedling development Neocarya macrophylla, a species of oleaginous Niger. The treatments applied to seed have a waiting time shorter than the untreated seeds. The control has a staggered germination (30 days) and shelling of nuts influenced seed germination bundled (16 days). Unprocessed nuts are the best germination rate (89.53%). Soaking nuts during 72 h and 120 h is fatal for germination. The shelf life has significant effects on the germination of walnuts and almonds. The observation shows a germinating seed cryptogeal. The low germination rates nuts without water shows that water is a limiting factor to the spread of this tree species. The seedlings are very sensitive to dampingoff and tolerant enough to transplantation with a survival rate of 79%.